A Comparative Study of Patriarchal Subjugation in Eliot’s and Edrisis’s novels - Arian, Ali (Opción, 2019)
This paper is going to through light on the representation of women‟s subjugation in patriarchal societies (East and West) through an analysis of the women characters in Eliot‟s (1871) Middlemarch and Alizadeh‟s (2008) “The House of The Edrisis”.As a method, two novels from two different societies and through finding the elements of subjugation in patriarchal societies are chosen as a comparative case study analysis. The study mostly focuses on the analysis of the female subordination with educational, vocational and social extensions and their expectations of marriage in the time of the novels that is mostly Pre-Victorian era.